Kualitas dan Aktifitas Antibakteri Dadih Susu Sapi Mutan Lactococcus lactis terhadap Staphylococcus aureus, Escherechia coli dan Salmonella typii - S. Melia; I. Juliyarsi (Universitas Andalas, 2011)
Lactococcus lactis mutant dadih is fermented food made of cow's milk in a plastic tube with a 2% Lactococcus lactis and incubated at 30oC for 48 hours. The experiment result shown, the characteristics dadih barriers Lactococcus lactis mutants on antimicrobial activity against Staphylococcus aureus wider than antimicrobial activity against Escherechia typii coli and Salmonella. Lactococcus lactis mutant dadih contains 71,4% water, 0,93% acidity , 5:02% protein , 6:39% fat, 18 x 105 cfu / g total colony of Lactococcus lactis mutant, and essential amino acid.